Phase I/II Study of Capmatinib Plus Erlotinib in Patients With MET-Positive Non–Small-Cell Lung Cancer. (2021) - McCoach, Caroline E.; Yu, Aiming; Gandara, David R.; Riess, Jonathan W.; Vang, Daniel P.; Li, Tiahong; Lara, Primo N.; Gubens, Matthew; Lara, Frances; Mack, Philip C.; Beckett, Laurel A.; Kelly, Karen
Abstract : PURPOSE: MET dysregulation is an oncogenic driver in non–small-cell lung cancer (NSCLC), as well as a mechanism of TKI (tyrosine kinase inhibitor) resistance in patients with epidermal growth factor receptor ( EGFR )–mutated disease. This study was conducted to determine safety and preliminary efficacy of the combination EGFR and MET inhibitors as a strategy to overcome and/or delay EGFR-TKI resistance. METHODS: A standard 3 + 3 dose-escalation trial of capmatinib in combination with erlotinib in patients with MET-positive NSCLC was used. Eighteen patients in the dose-escalation cohort received 100-600 mg twice daily of capmatinib with 100-150 mg daily of erlotinib. There were two dose-expansion cohorts. Cohort A included 12 patients with EGFR -mutant tumors resistant to TKIs. Cohort B included five patients with EGFR wild-type tumors. The primary outcome was to assess safety and determine the recommended phase II dose (RP2D) of the combination. RESULTS: The most common adverse events of any grade were rash (62.9%), fatigue (51%), and nausea (45.7%). Capmatinib exhibited nonlinear pharmacokinetics combined with erlotinib, while showing no significant drug interactions. The RP2D was 400 mg twice daily capmatinib tablets with 150 mg daily erlotinib. The overall response rate (ORR) and DCR in dose-expansion cohort A was 50% and 50%, respectively. In cohort B, the ORR and disease control rate were 75% and 75%. CONCLUSION: Capmatinib in combination with erlotinib demonstrated safety profiles consistent with prior studies. We observed efficacy in specific patient populations. Continued evaluation of capmatinib plus EGFR-TKIs is warranted in patients with EGFR activating mutations.